New trends on microbiological water treatment. - Heidarpour, Farideh; Wan Ab. Karim Ghani, Wan Azlina; Ahmadun, Fakhru'l-Razi; Sobri, Shafreeza; Torabian, A.; Heydarpour, V.; Zargar, Mohsen (National Institute R and D of Materials Physics, 2011)
Silver nanoparticle-decorated porous polypropylene filter is prepared by physical vapor deposition method using a modified Balzers 760 coating machine. Silver nanoparticles were generated by electron beam bombardment of the silver metal. A 45nm layer of the silver nanoparticles were subsequently deposited on the polypropylene filter homogenously. The nano silver-coated filters were characterized using scanning electron microscopy, transmission electron microscopy and atomic force microscopy. The antibacterial efficiency of the nano silver-coated filters was evaluated using a custom- made experimental set up and the membrane filter method. A zone of inhibition test was also performed to compare the bactericidal effect of coated versus non-coated filters. At a flow rate of 3L/hr, the output count of Escherichia coli was zero after 6.5 hours filtration when the input water had a bacterial load of 103 colony-forming units (cfu) per milliliter. The inductively coupled plasma/mass spectrometry (ICP/MS) results showed that the 45nm layer of the silver nanoparticles are stable on the water filter and are not washed away by water flow even after 6.5h filtration.